Modular sovereignty, security and debt: The excessive deficit procedure of the European Union - Andreas Langenohl (Finance and Society, 2017)
The Excessive Deficit Procedure (EDP) is a political mechanism that aims at "multilevel governance" of state indebtedness in the European Union. As such, it has become the concern of research that asks how sovereignty becomes articulated in this process. This article approaches this question through the conceptualization of a modular notion of sovereignty elaborated through a discussion of work on the finance-security nexus. The article argues that existing accounts of the formation of sovereign power in relation to state debt can be combined into a notion of modular sovereignty when seen through the prism of critiques of contractualism that take issue with liberal notions of state sovereignty and credit security. This way, the indebted state becomes visible as the referent object of multiple, and potentially contradictory, invocations of sovereignty as exercised in the EDP. First, it figures as the seat of budget sovereignty, holding its social substrate liable for its debts while ignoring inequalities in that substrate. Second, it is appealed to, within a biopolitical rationality, as the sovereign guarantor of the financial wellbeing of its population. Third, it is seen as the executor of financial wisdom that is mobilized in struggles between different levels of financial governance in the EDP.
Keywords: 300; European Union; Excessive Debt Procedure; sovereignty; sovereign debt; contractualism